Design trade-offs in amorphous indium gallium zinc oxide thin film transistor based bio-signal sensing front-ends. (9th January 2019) - Zulqarnain, Mohammad; Stanzione, Stefano; van der Steen, Jan-Laurens P J; Gelinck, Gerwin H; Abdinia, Sahel; Cantatore, Eugenio
Abstract: With the advent of the Internet of things, wearable sensing devices are gaining importance in our daily lives for applications like vital signal monitoring during sport and health diagnostics. Amorphous indium gallium zinc oxide (a-IGZO) thin film transistors (TFTs) fabricated on flexible large-area substrates are a very interesting platform to build wearable sensing devices due to their flexibility, conformability to the human body, and low cost. For this paper four different bio-signal sensing front-end circuits based on a-IGZO TFTs are designed, fabricated, measured and compared, focusing on three performance indicators which are in a trade-off: power efficiency factor (PEF), area occupation and input impedance. Considering a 200 Hz bandwidth, the measured PEF varies between 4.7 × 10 5 and 7.5 × 10 6 . The area occupation spans from 4.2 to 37 mm 2, while the input impedance at 1 Hz varies from 5.3 to 55.3 MΩ. The front-ends based on diode-load amplifiers are compact but have the lowest input impedance and need external capacitors; a front-end exploiting positive feedback impedance boosting has the highest input impedance and is fully integrated on foil, but occupies the largest area.